(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Due to continuous improvement of the quality and therefore fully satisfy the needs and expectations of each partner (customers, staff and other stakeholders) and also maintain competitive advantage. It becomes necessary to implement different quality improvement initiatives like Total Quality Management, ISO certification, Agile & Lean manufacturing etc. But these initiatives are not profitability as well as time efficient in terms of quality so introducing and implementing the Six Sigma methodologies was proven to provide breakthrough quality improvements in a reasonable short time. This paper present manufacturing process improvement through DMAIC Six Sigma methodology